2014
DOI: 10.1128/aac.03393-14
|View full text |Cite
|
Sign up to set email alerts
|

A First-in-Human Randomized, Double-Blind, Placebo-Controlled, Single- and Multiple-Ascending Oral Dose Study of Novel Antimalarial Spiroindolone KAE609 (Cipargamin) To Assess Its Safety, Tolerability, and Pharmacokinetics in Healthy Adult Volunteers

Abstract: This first-in-human randomized, double-blind, placebo-controlled, ascending-single and -multiple oral dose study was designed to evaluate the safety, tolerability, and pharmacokinetics in healthy volunteers of KAE609 (cipargamin; formerly NITD609), a spiroindolone now in trials for malaria treatment. It was studied in single-dose cohorts (1 to 300 mg, including one 30-mg food effect cohort) with 4 to 10 subjects in each cohort and in multiple-dose cohorts (10 to 150 mg once daily for 3 days) with 8 subjects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 21 publications
2
43
0
Order By: Relevance
“…These phenotypic screenings have identified new active compounds, and some of them (KAE609 [45], OZ439 [46]) are currently in clinical development. To achieve the goal of malaria eradication proposed by the scientific community, the same approach should be applied to parasite stages, responsible for transmission.…”
Section: Discussionmentioning
confidence: 99%
“…These phenotypic screenings have identified new active compounds, and some of them (KAE609 [45], OZ439 [46]) are currently in clinical development. To achieve the goal of malaria eradication proposed by the scientific community, the same approach should be applied to parasite stages, responsible for transmission.…”
Section: Discussionmentioning
confidence: 99%
“…1), a spiroindolone, represents a new class of potent, fast-acting, schizonticidal agents Yeung et al, 2010;Meister et al, 2011;Spillman et al, 2013). KAE609 was safe and well tolerated in healthy subjects up to the highest tested single dose of 300 mg and the highest tested multiple dose of 150 mg daily for 3 days (Leong et al, 2014). Evaluation in 21 evaluable adult patients with uncomplicated malaria due to either P. vivax (n = 10) or P. falciparum (n = 11) showed that once-daily dosing of KAE609 at 30 mg for 3 days was well tolerated and resulted in a rapid median parasite clearance time of approximately 12 hours for both P. vivax and P. falciparum (White et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…1; Yeung et al, 2010), a spiroindolone, represents a new class of potent, fast-acting, schizonticidal agents for the treatment of malaria Meister et al, 2011;Spillman et al, 2013). More recently, KAE609 was shown to be safe and well tolerated in healthy subjects up to a single dose of 300 mg and multiple doses of 150 mg daily for 3 days (Leong et al, 2014). Evaluation in 21 adult patients with uncomplicated malaria due to either Plasmodium vivax (n = 10) or Plasmodium falciparum (n = 11) showed that once-daily dosing of KAE609 at 30 mg for 3 days resulted in a rapid median parasite clearance time of approximately 12 hours for both P. vivax and P. falciparum (White et al, 2014).…”
Section: Introductionmentioning
confidence: 99%